Impact of information and in-home sensory exposure on liking and willingness to pay: The beginning of Fairtrade labeled coffee in France. (October 2015) - Lange, C.; Combris, P.; Issanchou, S.; Schlich, P.
Abstract: This study was conducted to assess how the Fairtrade label interacts with the perception of intrinsic product characteristics on liking and purchase decisions and to estimate the evolution of this interaction after exposure to coffees and/or exposure to ethical information. In the first session, 119 consumers gave liking scores for 2 regular and 2 Fairtrade coffees under a blind tasting condition. Then, they were asked to indicate the maximum price they would pay for each product in 2 auctions taking place under different information conditions. In the first auction, participants saw the packaging but did not taste the coffee; in the second auction, they could both taste the coffee and see the packaging. After the first session, the consumers were randomly split into 4 groups, and these groups were exposed for one month to different conditions before returning to the lab for exactly the same measurements as in the first session. The first of the 4 groups was not exposed to sensory characteristics or ethical information. Each consumer of the second group was only exposed to sensory characteristics of the coffees (one packet of his/her least liked regular and ethical coffees delivered in blind packaging for home consumption). The third group was exposed to sensory characteristics and ethical information (the same as the second group but using the original coffee packaging showing fair trade information). The final group was only exposed to ethical information. Results showed that the hedonic scores of the least liked ethical and regular products increased from sessions 1 to 2, but not significantly more when consumers were exposed to these products between the sessions. However, while consumers offered lower prices for ethical products at the first session, those who were exposed to ethical information increased their willingness to pay for ethical products. This effect became statistically significant when consumers could taste the products before making their bid. The effect of exposure to ethical information was also transferred to the willingness to pay for the ethical product to which the consumers were not exposed. This study highlights the interest of a design, which makes it possible to assess the impact over time of sensory and external information on the willingness to pay. Highlights: To assess the impact over time of sensory and external information on willingness to pay Consumers were not ready to pay more for Fairtrade coffees on the basis of packaging. Consumers were even ready to pay less for Fairtrade coffees when they could taste them. Willingness to pay for Fairtrade coffees increased after exposure to ethical information. Ethical information had more effect when consumers tasted coffees before making their bid.